Efektywność zmian w ukraińskim systemie wyborczym w procesie transformacji - Sydun, Swietłana (Wydział Nauk Politycznych i Dziennikarstwa UAM w Poznaniu, 2011)
Over the period of its independence, Ukraine has gone through several stages of modernization of its electoral system, moving from system of absolute and mixed majority to proportional representation. What can this signify? Either the democratic principles of the national political system are strengthening and political institutions fully function in society, or a system of state authorities has actually transformed into the rule of oligarchic parties which control the activities of the government via parliament and are sufficiently independent from the President. By virtue of the constitutional reform from late 2004, Ukraine has transformed into a parliamentary-presidential republic, where the parliament is the core of control over executive power. Therefore, it is quite significant which parties win the elections.
Keywords: Ukraina; system wyborczy; transformacja ustrojowa